In the master's eye - Tracy, Susan Jean (Univ. of Massachusetts Press, 1995)
This book explores the way in which literature can be used to reinforce social power. Through rigorous readings of a series of antebellum plantation novels, Susan J. Tracy shows how the narrative strategies employed by proslavery Southern writers served to justify and perpetuate the oppression of women, blacks, and poor whites Tracy focuses on the historical romances of six authors: George Tucker, James Ewell Heath, William Alexander Caruthers, John Pendleton Kennedy, Nathaniel Beverley Tucker, and William Gilmore Simms. Using variations on a recurring plot - in which a young planter/hero rescues a planter's daughter from an
Keywords: Blancs de la classe ouvrière dans la littérature; Classes sociales dans la littérature; Femmes et littérature - États-Unis (Sud) - Histoire - 19e siècle; Littérature américaine - 19e siècle - Histoire et critique; Littérature américaine - États-Unis (Sud) - Histoire et critique; Littérature et société - États-Unis (Sud) - Histoire - 19e siècle; Noirs américains dans la littérature; Patriarcat dans la littérature; Pauvres dans la littérature; Écrits d'hommes américains - Histoire et critique; États-Unis (Sud) dans la littérature; Geschichte; African Americans in literature; American literature; Literature and society; Patriarchy in literature; Poor whites in literature; Social classes in literature; Women and literature; Working class whites in literature; Weiße; Frau; Schwarze; Armut; Literatur